Pre-adoption of KMS: user acceptance from knowledge worker perspectives - Assegaff, S. (IEEE, 2012)
Non-technological problem has been identified as main barriers in knowledge management implementation. Culture and people have been identified as main barriers. Lack of understanding the benefit of using knowledge management system (KMS) makes people unaware about KMS. There are two types of knowledge workers which have different belief in KMS benefit. Benefit from the knowledge seekers perspective will be different with knowledge contributors. Current KMS acceptance model focus in evaluate and understand the user acceptance from knowledge seeker perspective. There is a lack of models that can be used to evaluate and understand user from both knowledge seeker and contributor perspective. Thus, this study proposes a modified model to understand both knowledge worker acceptances of KMS.